(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Therapeutic drug monitoring of vancomycin is an important issue in clinical decision-making and dosage modifying, particularly among patients in critical conditions and decreased kidney function. Urine is typically readily available in hospitalized patients and therapeutic drug monitoring in urine may be a reliable and noninvasive procedure compared to frequent blood sampling. We aimed to determine and validate the diagnostic yield of vancomycin trough level in urine. Materials and Methods. In a prospective study, 95 patients who were treated with vancomycin for any clinical condition were enrolled in this study. Patients were divided into 2 groups according to their glomerular filtration rate (greater than 80 mL/min/1.73 m2 versus 15 mL/min/1.73 m2 to 80 mL/min/1.73 m2). Vancomycin serum trough levels and simultaneous urine trough levels were detected by high-pressure liquid chromatography. Results. The mean serum and urine trough levels of vancomycin were 13.13 ± 1.34 mg/L and 7.79 ± 1.23 mg/L, respectively. The serum and urine trough levels had a positive linear correlation (r = 0.38, P < .001), which was also significant in patients with normal kidney function (r = 0.43, P = .001). The estimated serum concentration was equal to urine vancomycin concentration plus 5.3 mg/L. Conclusions. Urine levels of vancomycin correlate with simultaneous serum levels and may consistently predict serum levels in patients with normal kidney function. Therefore, urine vancomycin monitoring might be used as a noninvasive alternative to blood sampling, particularly in patients with normal kidney function.